Comparação dos marcadores sorológicos em grupo de doadores de sangue que fizeram ou não uso do voto de auto exclusão na Fundação HEMOAM (2010-2013) - Souza, Janaina Carmo de (2015)
SOUZA, JC Comparison of serological markers in group of blood donors who did or did not use the confidential unit exclusion in HEMOAM Foundation (2010-2013). Master's Dissertation - Hemoam Foundation / University of Amazonas, Manaus, 2015. Introduction: Transfusional safety is considered a priority in blood banks worldwide and is highly dependent in the proper selection of healthy donors while the ones with high risk of infections that may be transmitted by transfusions need to be avoided. Significant advances in serologic testing have improved safety for blood recipients, especially the implementation of nucleic acid tests (NAT) for HIV and HCV and more recently for HBV, which reduce the immunological window period and the risk of transmission by transfusion. Among alternatives to improve blood donors safety is the use of confidential sel-exclusion form (CSE) by which the donor can ask to exclude his blood for donation without any explanation while maintaining the serologic testing. In a reference public health blood bank in the Brazilian Amazon (Hematology and Hemotherapy Foundation/FHEMOAM, Manaus) the CSE form was introduced in 2010 and became mandatory in 2011. Objectives: This study evaluated socio-demographic and serologic profiles of donors who used CSE forms and its utility at FHEMOAM. Methods: A descriptive study of donors who used CSE and a case-control study comparing donors using or not CSE (1:4) were conducted at FHEMOAM (June 2010-December 2011). Serologic screening included: HCV (ELISA, NAT HCV), HIV (ELISA, NAT HIV), HBV (ELISA, NAT HBV), Chagas Disease (ELISA), Syphilis (VDRL) and HTLV I/II (ELISA). Categorical and numerical variables were analyzed considering a significance level of 0.05. Results: During the study period 175.275 donations were performed at FHEMOAM and 1.426 (0.81%) used CSE forms. Among CSE-donors the median age was 30 years and males (83.6%), single (64.2%), repeat donors (62.6%), voluntary donations (54%) predominated; 8.5% had at least one positive test in the serologic screening. Overall a similar frequency of positive serology for at least one pathogen was observed among cases and controls (3.01% and 2.38%, respectively). However, compared to controls, CSE- donors presented a higher frequency of positivity in both serologic tests used to screen HIV infection (test 1 OR=2.23, CI 95% 1.18 - 4.21, p= 0.012; test 2 OR=1.96, CI 95% 1.13 – 3.40, p=0.015). Considering confirmatory results, the risk of HIV infection in CSE donors was 2.95 times higher compared to controls (OR=2.95, CI 95%1.34 – 6.43, p= 0.012). No case of coinfection was detected in case or controls Conclusions: The current study revealed a 3 times higher risk of confirmed HIV infection among CSE-donors at FHEMOAM during the study period indicating that CSE forms represent an additional and valid tool to guarantee transfusional safety for donors and patients that use hemocomponents produced by this institution.